Species Classification and Molecular Studies of Bile Salt Hydrolase (BSH) Gene in Bifidobacterium Spp - Mustafa, Shuhaimi (2003)
Molecular methods were used to identify and characterise Bifidobacterium isolated from the faeces of breast-fed infants. A Bifidobacterium genus-specific primers based on the V9 variable region of the 168 rDNA was used to identify Bifidobacterium isolates and to distinguish them from other genera. All the Bifidobacterium species tested generated PCR product with the size of approximately 1.35 kb, whereas other genera showed no band with these primers. Furthermore, a sequence analysis of 168 rRNA gene of Bifidobacterium isolates revealed high homology (98% and above) with Bifidobacterium pseudocatenulatum JCM1200. This result indicates that the 16S rRNA gene sequence analysis is a useful and accurate tool for the identification of the genus Bifidobacterium In addition, a set of B. pseudocatenulatum species-specific primer was used as an alternative to identify the species of B. psedocatenulatum using PCR technique. It was found that this set of primer was able to generate PCR product with the size of approximately 278 bp in all the B. pseudocatenulatum isolates as well as the type strain of B. pseudocatenulatum JCM1200. Other species of bifidobacteria gave no band. A protocol for the rapid fingerprinting technique of Bifidobacterium strains and other pro biotic microorganisms based on randomly amplified polymorphic DNA (RAPD) has been developed. Three 10-mer primers (GEN1-60-03, GEN1-60-06 and GEN1-60-07) used generated RAPD patterns with DNA fragments ranging from approximately 0.3 kb to 10.0 kb in size. Examination of the DNA fingerprints using cluster analysis showed a significant genetic diversity among the strains tested. Another fingerprinting technique based on the distribution of dispersed repetitive DNA [enterobacterial repetitive intergenic consensus (ERIC) and repetitive extragenic palindromic (REP)] segments in the genome of Bifidobacterium and other pro biotic bacteria was also examined for the first time using primers derived from the REP and ERIC sequences and PCR. The patterns of the resulting PCR products were analysed on agarose gel and were found to be highly specific for each species. All the B. pseudocatenulatum isolates and B. pseudocatenulatum JCM 1200 type strain presented an approximately 1.5 kb fragment by ERIC and a 800 bp fragment by REP. These two fragments were not detectable in other species of bifidobacteria. This study demonstrates the presence of ERIC and REP-like elements in the genome of bifidobacteria and other probiotic bacteria. PCR technique was also used to detect the presence of bsh gene in Bifidobacterium longum B8536. In this regards, a pair of PCR primers for the rapid detection of bsh gene from B. longum have been synthesised and have revealed the bsh gene of appoximately 970 bp. The bsh gene was cloned and sequenced showing a high homology to bsh gene previously published. The resulting nucleotide sequence encodes a predicted protein of 317 amino acids with a molecular weight of approximately 35 kDa. The bsh gene from B. longum was also cloned and expressed in E. coli BL21-S1 using pRSET -A expression vector. The expressed protein was detected using immunoblot assay.